Technical and managerial guidelines for vasectomy services - World Health Organization (Geneva : WHO, 1988)
Presents practical guidelines covering subjects important to the development, management, and operation of high-quality vasectomy services. The opening chapters, which are addressed to programme managers and administrators, provide basic information about the procedure, its advantages and disadvantages, and the factors, such as caseload and staffing, that should be considered when organizing and managing a vasectomy service. The importance of public information and communication, including client assessment and counselling, is also discussed. The second group of chapters presents technical information about the procedure, requirements for pre- and post-operative care, complications, effectiveness, possibilities for reversal, the necessary instruments and equipment, and the training requirements of clinic staff, including surgeons. Additional practical information is presented in a series of 7 annexes, where readers will find assistance in the form of a sample question-and-answer brochure for vasectomy clients, sample post-operative instructions, an inventory of the contents of standard vasectomy kits, and a model curriculum for a vasectomy training programme.
Keywords: Vasectomy -- standards; Vasectomy -- methods